Modeling and Using Context 6th International and Interdisciplinary Conference, CONTEXT 2007, Roskilde, Denmark, August 20-24, 2007, Proceedings - Kokinov, Boicho; Richardson, Daniel C.; Roth-Berghofer, Thomas R.; Vieu, Laure; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Context a?ects a wide range of activities in humans and animals as well as in arti?cialagentsandothersystems.Theimportanceofcontextiswidelyackno- edged, and “context” has become an area of study in its own right, as evidenced bynumerousworkshops,symposia,seminars,andconferencesonthisarea.CON- TEXT,theoldestconferenceseriesfocusing oncontext,is unique inits emphasis on interdisciplinary research. Previous CONTEXT conferences have been held in Rio de Janeiro, Brazil (CONTEXT’97), Trento, Italy (CONTEXT’99, LNCS 1688), Dundee, UK (CONTEXT 2001, LNCS 2116), Palo Alto, USA (CON- TEXT 2003, LNCS 2680), and Paris, France (CONTEXT 2005, LNCS 3554). Each of these brought together researchers and practitioners from a large range of ?elds to discuss and report on context-related research and projects. The CONTEXT 2007 conference was held at Roskilde University, Denmark. The ?rst two days were devoted to workshops on speci?c areas of interest to the context community and, in parallel, the doctoralconsortium. The remaining three days featured invited talks, presentations, and posters on both theoretical and applied context research. This volume contains the papers presented at CONTEXT 2007, the Sixth International and Interdisciplinary Conference on Modeling and Using Context. There were 121 submissions to the conference. The committee decided to accept 42 papers on the basis of a thorough and highly selective review process. We believe that the papers of this volume represent a snapshot of current work and contribute to both theoretical and applied aspects of research.
Default Inferences in Metaphor Interpretation -- MDD Approach for the Development of Context-Aware Applications -- Of Situations and Their Neighbors -- Conceptual Analysis of Interdisciplinary Scientific Work -- Towards a Methodology for Context Sensitive Systems Development -- Meaning, Contexts and Justification -- Local Context Selection for Aligning Sentences in Parallel Corpora -- Context in Use for Analyzing Conversation Structures on the Web Tied to the Notion of Situatedness -- Using Context for the Extraction of Relational Views -- Context Modeling: Task Model and Practice Model -- Context Modeling: Context as a Dressing of a Focus -- Service-Context Unified Knowledge Representation for Autonomic Adaptation -- Goal Reasoning with Context Record Types -- Context-Oriented Domain Analysis -- A Semantics for Changing Frames of Mind -- The Influence of Task Contexts on the Decision-Making of Humans and Computers -- Context and Design Agents -- On Relating Heterogeneous Elements from Different Ontologies -- ReCQ: Real-World Context-Aware Querying -- Objective vs. Subjective Scales: The Challenge That the Scale Type Poses to the JUDGEMAP Model of Context Sensitive Judgment -- Similarity Measurement in Context -- Delimited Continuations in Operating Systems -- Explanations and Context in Ambient Intelligent Systems -- Context-Sensitivity of Human Memory: Episode Connectivity and Its Influence on Memory Reconstruction -- Enhancing Just-in-Time E-Learning Through Machine Learning on Desktop Context Sensors -- Coping with Unconsidered Context of Formalized Knowledge -- OCCAM: Ontology-Based Computational Contextual Analysis and Modeling -- User Profiling with Hierarchical Context: An e-Retailer Case Study -- Context-Aware Security Management System for Pervasive Computing Environment -- VIVACE Context Based Search Platform -- AcroDef: A Quality Measure for Discriminating Expansions of Ambiguous Acronyms -- Risk Context Effects in Inductive Reasoning: An Experimental and Computational Modeling Study -- Representing Context in Web Search with Ontological User Profiles -- Thai Text Coherence Structuring with Coordinating and Subordinating Relations for Text Summarization -- Three Interactions Between Context and Epistemic Locutions -- Do You Believe What Eye Believe? -- Investigating the Specifics of Contextual Elements Management: The CEManTIKA Approach -- Distributed Document Contexts in Cooperation Systems -- Integrating Engineering, Cognitive and Social Approaches for a Comprehensive Modeling of Organizational Agents and Their Contexts -- Fields as Dimensions of Context: An Application of Bourdieu’s Sociological Theory to Modelling of Context of Social Action -- Context Sensitivity: Indexicalism, Contextualism, Relativism -- An Operational Definition of Context.
Keywords: Artificial intelligence; Computer simulation; Mathematical logic; Application software; Artificial Intelligence; Simulation and Modeling; Mathematical Logic and Formal Languages; Computer Appl. in Social and Behavioral Sciences; Computer Appl. in Arts and Humanities